The working times they are a-changing: Trends in six EU countries (1992-2022) - Sergio Torrejón Pérez; Enrique Fernández-Macías; Ignacio González Vázquez; Ildefonso Marqués Perales (European Commission, Joint Research Centre (JRC), 2024)
The time Europeans devote to paid work has consistently decreased since the Industrial Revolution. However, since the 1980s, the pace of this trend has slowed. The aim of this article is twofold: first, we develop a theoretical framework to account for the main factors determining the evolution and distribution of working hours in Europe; second, we utilize EU-LFS data (1992-2022) to analyze the primary factors explaining recent developments in working time. Our results indicate: 1) that reductions in working hours are primarily attributable to the increased prevalence of non-standard forms of work, mainly part-time; 2) that part-time work has expanded mainly due to the feminization of employment and the tertiarization of the economy; 3) that full-time workers continue to work approximately the same hours as in the 1980s, as countervailing effects push working hours up (occupational upgrading and tertiarization) and down (the expansion of public services, the shrinking of the goods-producing sector, and self-employment becoming less time-intensive); and 4) that the self-employed work fewer hours over time because part-time self-employment has become more prevalent, although the self-employed still work the longest hours on average. The theoretical and empirical implications arising from these findings are discussed, along with potential avenues for future research.
Keywords: 330; employment; labour; working time; work intensity